How Does Pyridoxamine Inhibit the Formation of Advanced Glycation End Products? The Role of Its Primary Antioxidant Activity - Rafael Ramis; Joaquín Ortega-Castro; Carmen Caballero; Rodrigo Casasnovas; Antonia Cerrillo; Bartolomé Vilanova; Miquel Adrover; Juan Frau (MDPI AG, 2019)
Pyridoxamine, one of the natural forms of vitamin B6, is known to be an effective inhibitor of the formation of advanced glycation end products (AGEs), which are closely related to various human diseases. Pyridoxamine forms stable complexes with metal ions that catalyze the oxidative reactions taking place in the advanced stages of the protein glycation cascade. It also reacts with reactive carbonyl compounds generated as byproducts of protein glycation, thereby preventing further protein damage. We applied Density Functional Theory to study the primary antioxidant activity of pyridoxamine towards three oxygen-centered radicals (•OOH, •OOCH3 and •OCH3) to find out whether this activity may also play a crucial role in the context of protein glycation inhibition. Our results show that, at physiological pH, pyridoxamine can trap the •OCH3 radical, in both aqueous and lipidic media, with rate constants in the diffusion limit (>1.0 × 108 M <semantics> − 1 </semantics> s <semantics> − 1 </semantics> ). The quickest pathways involve the transfer of the hydrogen atoms from the protonated pyridine nitrogen, the protonated amino group or the phenolic group. Its reactivity towards •OOH and •OOCH3 is smaller, but pyridoxamine can still scavenge them with moderate rate constants in aqueous media. Since reactive oxygen species are also involved in the formation of AGEs, these results highlight that the antioxidant capacity of pyridoxamine is also relevant to explain its inhibitory role on the glycation process.